An easy way for the hydrolysis, pre-concentration, and chemical stabilization of crocetin from saffron powder. (30th May 2022) - Fiorito, Serena; Palumbo, Lucia; Epifano, Francesco; Collevecchio, Chiara; Cardellini, Fabio; Bastianini, Maria; Spogli, Roberto; Genovese, Salvatore
Highlights: Sorbents have been used for the adsorption of crocetin from saffron powder. Zinc hydroxy chloride largely and selectively adsorbed crocetin. Percentages of adsorbed crocetin were evaluated by HPLC analysis. Abstract: To date there are no methods in the literature leading to crocetin selective concentration from saffron powder aqueous solutions. To this aim, we decided to test the performance of its heterogeneous extraction by means of a panel of 21 synthetic clays, 4 of which demonstrated to selectively retain crocetin in the solid phase after hydrolysis of its digentiobyosil ester (crocin) (and its isomers) and to its chemical stabilization (e.g., oxidation) over time. The best adsorption yield was obtained with zinc hydroxy chloride (66.18 ± 0.06 μg/g dry powder). This phenomenon was assessed by HPLC-DAD analyses after desorption of crocetin from the respective support and assessing its degradation along a period of 30 days. The method we established could represent a good mean to provide pure crocetin from saffron powder, preserving in the meantime its chemical properties for a concrete future exploitation for food pharmaceutical, and cosmetic purposes.